USE VS. ABUSE OF SPECIAL INVESTIGATIVE MEASURES IN DETECTING SEVERE FORMS OF CRIME IN REPUBLIC OF MACEDONIA - Budjakoski, Stefan; Todorovska, Natasha (European Scientific Journal, ESJ, 2014)
The reformed Macedonian penal judiciary system is as concept a result of adjusting the development of the social system, which originated more than a century ago. Throughout the long history the penal system was, more or less successfully, adjusted to significant historical, political and social changes. The point of reference for the penal and legal reform is harmonization with the international standards on human rights and constitutionalism on one hand, and the increase of crime and corruption on the other. The development of the international law on human rights also had influence on the increase of the penal and legal protection, which resulted in harmonization of our legislation by embedding the international norms on human rights. The European Convention on Human Rights, which is considered to be the main instigator of the reforms of the penal procedure in the last ten years, also had significant influence on the law and the legal practice. With reference to a clearly defined and consistent reform concept, corroborated by solid comparative and empirical examinations, and comparisons with foreign experience, successful reforms of the penal judiciary have been initiated in the Republic of Macedonia. Comprehensive reform of the penal system must be planned and carried out exclusively based on rational and confirmed means and methods of detection, and elimination of all dysfunctional elements of the organization and the operation of the public prosecution, police and judiciary.